Modelling and reconstruction of gabor-type holograms. (2011)
The processes of modelling and reconstruction of holograms are based on the calculation of the diffraction integral either on its kirchhoff-fresnel or rayleight-sommerfeld formulation. Numerically, such an integral can be evaluated via different approaches: the convolution theorem, angular spectrum, and fresnel transform, among others. In this paper, the modelling of gabor-type in-line holograms of opaque particles of different diameters is presented. Those holograms are thereafter reconstructed by the numerical evaluation of the diffraction process that a spherical wavefront undergoes when it illuminates the hologram. The modelling-reconstruction process is employed for studying the performance of digital in-line holographic microscopy while the concentration of a simulated monodispersed monolayer is varied.